On the Conversion of Bauxite Ores to Highly Activated Alumina Media for Water Remediation. (6th March 2019) - Haddad, Andrew Z.; Pilgrim, Corey D.; Sawvel, April M.; Hohman, James Nathan; Gadgil, Ashok J.
Abstract: Good quality drinking water is necessary to maintain a high quality of life. Millions lack access to clean and safe drinking water, and current trends suggest that billions will face acute water shortages in the coming decades. Development of new materials has led to technological impacts on water purification, from desalination membranes to atmospheric water scavenging. However, the most challenging aspect of technological solutions is cost: if the community being serviced cannot afford the solution, it is not likely to be sustainable. Repurposing Earth‐abundant materials to replace highly engineered solutions is an atractive solution. Herein, minimal processing of bauxite rocks produces a high‐porosity and reactive activated alumina in situ, without purification directly from the ore. This acid‐treated, thermally activated bauxite (ATAB) exhibits a high surface area of 401 ± 6 m 2 g −1, a 40‐fold increase relative to its parent ore, and a 2× increase relative to the state‐of‐the‐art fluoride adsorbent, activated alumina. The composition, preparation, and mechanism of adsorption are studied by X‐ray diffraction, X‐ray photoelectron spectroscopy, and multiple‐quantum magic‐angle spinning 27 Al nuclear magnetic resonance (NMR). The maximum adsorption density of ATAB is comparable with that of activated alumina, but ATAB requires fewer processing steps, thus warranting future consideration as a primary adsorbent of choice for fluoride removal from water. Abstract : Minimal processing of bauxite ores leads to a highly porous boehmite structure, which efficiently scavenges fluoride from aqueous solutions through an ion exchange mechanism.